Progress in creating a joint research agenda that allows networked long-term socio-ecological research in southern South America : addressing crucial technological and human capacity gaps limiting its application in Chile and Argentina - Anderson, Christopher B. (2012)
Since 1980, more than 40 countries have implemented long-term ecological research (LTER) programs, which have shown their power to affect advances in basic science to understand the natural world at meaningful temporal and spatial scales and also help link research with socially relevant outcomes. Recently, a disciplinary paradigmatic shift has integrated the human dimensions of ecosystems, leading to a long-term socio-ecological research (LTSER) framework to address the world's current environmental challenges. A global gap in LTER/LTSER only exists in the latitudinal range of 40–60°S, corresponding to Argentina and Chile's temperate/sub-Antarctic biome. A team of Chilean, Argentine and US researchers has participated in an ongoing dialogue to define not only conceptual, but also practical barriers limiting LTER/LTSER in southern South America. We have found a number of existing long-term research sites and platforms throughout the region, but at the same time it has been concluded an agenda is needed to create and implement further training courses for students, postdoctoral fellows and young scientists, particularly in the areas of data and information management systems. Since LTER/LTSER efforts in Chile and Argentina are incipient, instituting such courses now will enhance human and technical capacity of the natural science and resource community to improve the collection, storage, analysis and dissemination of information in emerging LTER/LTSER platforms. In turn, having this capacity, as well as the ongoing formalization of LTER/LTSER programs at national levels, will allow the enhancement of crucial collaborations and comparisons between long-term research programs within the region and between hemispheres and continents. For Spanish version of the entire article, see Online Supporting Information (Appendix S1).